Classical Minimally Invasive Necrosectomy or Percutaneous Drainage in Acute Necrotizing Pancreatitis. Does Changing the Order of the Factors Change the Result? - Uomo, Generoso (JOP. Journal of the Pancreas, 2010)
No abstract available.